Dinamika Konflik Kerja-Keluarga Pada Guru - Dewi, Luh Kusuma; Mawardi, Artiawati; Suvianita, Khanis (ANIMA Indonesian Psychological Journal, 2007)
Struggling for a better welfare in a teachers’ life is a never ending effort. It is interesting to explore teachers’ life in order to have information regarding how teachers cope with work-family conflict. Work-family conflict is a conflict that occurs because of imbalanced role between job and family. This study was aimed to explore antecedents of work-family conflict, effects of work-family conflict on family and work domains, and how to cope with work-family conflict in order to achieve life satisfaction. Informants were three female teachers and three male teachers, who were married and had at least one child living with them. Data were taken through an in-depth interview, which were then analyzed interpretively. Results revealed through naration, show different ways in coping with conflicts between female and male teachers. Perjuangan untuk menemukan kesejahteraan hidup para guru adalah usaha yang tidak pernah usai. Kehidupan seorang guru menjadi menarik untuk disimak, terutama dalam menemukan informasi bagaimana mereka mengatasi konflik kerja-keluarga. Konflik kerja-keluarga adalah suatu bentuk konflik yang terjadi karena adanya ketidakseimbangan tuntutan peran di pekerjaan dan keluarga. Tujuan penelitian ini adalah mengetahui bagaimana konflik kerja-keluarga terjadi, apa dampaknya pada pekerjaan dan keluarga, dan bagaimana mereka mengatasi konflik tersebut untuk mencapai kesejahteraan hidup. Informan adalah tiga orang guru perempuan dan tiga orang guru laki- laki yang menikah dan minimal mempunyai satu orang anak yang tinggal satu rumah dengan mereka. Data diperoleh melalui wawancara mendalam, yang kemudian dianalisis secara interpretif. Hasilnya dipaparkan secara naratif, yang menunjukkan adanya cara yang berbeda dalam mengatasi konflik antara guru perempuan dan guru laki-laki.